Analysis of microRNA expression and micronuclei frequency in workers exposed to vinyl chloride monomer in China. (August 2017) - Feng, Nan-nan; Fang, Yan; Zhang, Ya-nan; Xu, Xiao-wen; Li, Yong; Wang, Jin-wei; Li, Yong-liang; Brandt-Rauf, Paul; Xia, Zhao-lin
Aim: To identify differently expressed miRNAs associated with vinyl chloride monomer (VCM) and micronuclei (MN) frequency.Method: In discovery stage, we used microarray to detect miRNAs expression in peripheral blood lymphocytes between six low and six high VCM-exposed workers grouped by medium cumulative exposure dose. Then we validated four miRNAs using real-time quantitative reverse transcription PCR (qRT-PCR) and detected the micronuclei frequencies using cytokinesis-block micronucleus assay in 94 VCM-exposed workers and 53 healthy control subjects.Results & conclusion: We found eight miRNAs significantly downregulated and seven miRNAs upregulated (|Fold Change| >2; p < 0.05) in the high-exposure group through microarray. We validate that miR-222–3p, miR-146a-5p and miR-151a-5p were downregulated, while miR-22–3p was upregulated in VCM-exposed group (all p < 0.01). Furthermore, we found that expression of miR-22-3p was upregulated in the high micronuclei (MN) frequency subjects. In conclusion, our study suggested that these four miRNAs could be biomarkers of VCM exposure, and moreover miR-22–3p was correlated with MN frequency.